YouTube as a source of information on Helicobacter pylori: Content and quality analysis - UPRAK, TEVFİK KIVILCIM (My University, 2023)
Background: Helicobacter pylori infection is the most common cause of infectious diseases worldwide, and management is a current and vital problem for physicians and patients. One of the online platforms that people use most to access health information is YouTube. Therefore, this study aimed to evaluate the quality and reliability of H. pylori information videos on YouTube. Materials and Methods: The \"Helicobacter pylori\" keyword was searched with default filters on YouTube. Two hundred videos were evaluated. The source of videos was categorized as academic institutions, professional organizations, physicians, healthcare professionals other than physicians, health information websites, and independent users. The target audience of the videos was classified as patients and healthcare professionals. The Global Quality Scale (GQS), JAMA, and modified DISCERN video scores were obtained by taking the average of the scores given by the two authors. Results: Seventy-four videos were analyzed, and the median duration was 9.25 (range: 1.14–121) min. The target audience of 43 (58.1%) videos was healthcare professionals, and 31 (41.9%) videos were for patients. There was no correlation between likes, dislikes, views, and the quality-usefulness of the videos. Video characteristics such as duration, likes, number of views, and time since video upload day were not associated with the source. The JAMA and DISCERN scores were significantly higher in academic institutions than in other sources. Health information websites had a significantly higher GQS score than other video sources (p =.01). In comparison, there was no significant difference between the target audience (patients and healthcare professionals) in terms of JAMA, modified DISCERN, and GQS scores. Conclusions: YouTube has numerous videos for healthcare information nowadays. Although the quality and reliability of YouTube videos on H. pylori are average according to common scoring systems, we recommend videos produced by academic institutions and health information websites to inform patients.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Gastroenteroloji-(Hepatoloji); Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Medicine; Internal Medicine Sciences; Internal Diseases; Gastroenterology and Hepatology; Life Sciences; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; İmmünoloji; GASTROENTEROLOJİ VE HEPATOLOJİ; BULAŞICI HASTALIKLAR; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; IMMUNOLOGY; GASTROENTEROLOGY & HEPATOLOGY; INFECTIOUS DISEASES; Gastroenteroloji; Bulaşıcı hastalıklar; Gastroenterology; Infectious Diseases; healthcare; Helicobacter pylori; online learning; social media; YouTube; healthcare; Helicobacter pylori; online learning; social media; YouTube